Evaluation of Associated Structural and Chromosomal Abnormalities in Patients with Fetal Cerebral Ventriculomegaly Detected in Ultrasonographic Imaging - Cagliyan, Erkan; Ozmen, Samican; Saridas Demir, Sureyya; Aydin, Ceren; Bilen, Egehan; Guleryuz, Handan; Yasar, Elif; Ercal, Derya; Bora, Elcin; Cankaya, Tufan (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: Fetal cerebral ventriculomegaly is defined as enlarged cerebral lateral ventricles. The etiology of fetal cerebral ventriculomegaly is multifactorial. Aneuploidy in ventriculomegaly is detected especially in moderate and severe ventriculomegaly accompanied by structural anomalies. This study aims to evaluate patients with fetal cerebral ventriculomegaly for associated structural and genetic abnormalities and their obstetric and neonatal outcomes. STUDY DESIGN: This retrospective cohort study was conducted at Dokuz Eylul University Faculty of Medicine, Obstetrics and Gynecology Department between January 2009 and December 2019. Eighty-seven cases were included in the study and were evaluated for associated structural abnormalities. The results of genetic diagnostic tests were evaluated retrospectively. Postpartum information of the cases was obtained from the hospital records and neurodevelopmental development of the newborns was recorded. RESULTS: Patients were classified as mild, moderate, and severe ventriculomegaly. Concomitant structural abnormalities were observed in 64% of the patients. Corpus callosum agenesis was the most common abnormality. The incidence of accompanying anomalies in severe ventriculomegaly was found to be significantly higher. Invasive prenatal tests were performed on 27 patients and one of them had a chromosomal abnormality. No significant correlation was observed between the incidence of postpartum neurodevelopmental disorders and the degrees of ventriculomegaly. CONCLUSIONS: Fetal cerebral ventriculomegaly is a dynamic process. The etiology is multifactorial and abnormalities can be detected during follow-up. All patients should be evaluated carefully for associated abnormalities. The cases should also be evaluated for neurodevelopmental outcomes after birth. All diagnosis, follow-up, and treatment options should be handled with a multidisciplinary approach.